Electron-vibron coupling in halogenated acenaphthenequinone upon O K-edge soft x-ray absorption - Schmidt, Norman Anja; Clark, Timothy; Urquhart, Stephen G.; Fink, Rainer (Journal of Chemical Physics, 2011)
We present high resolution oxygen K near-edge x-ray absorption spectra of the acenaphthenequinone (ANQ) derivative 3,8-dibromo-5,6-dichloro-ANQ (Br Cl-ANQ). The spectral features exhibit an almost identical vibronic fine structure compared to that shown by ANQ. The unequal distances of the vibronic levels as derived from the least-squares fit analysis of the vibronic progressions allows us to determine the anharmonicity of the excited state potentials involved. We conclude that a single vibrational progression couples to the resonant excitation of O 1s core electrons preferentially. Comparison of the two ANQ derivatives gives a clear indication that the vibronic mode corresponds to a C=O stretching mode, rather than coupling to a C-H mode as suggested previously. These conclusions are supported by density functional theory calculations. © 2011 American Institute of Physics.